Board Games in the CLIL Classroom New Trends in Content and Language Integrated Learning (Trends in Applied Linguistics [TAL], 2023)
The present book explores how modern board gaming and language teaching can be beneficially combined to achieve optimal impact. Modern board games have a lot to offer language learners and teachers, and they should play a much more significant role in what has been labelled "Content and Language Integrated Learning" or CLIL. Modern board games require cooperation, problem-solving, active discovery, interpretation and analysis. Most importantly, modern board games allow students to explore a hypothetical environment without the risk of language errors. The key ingredient of the present book is "game-based learning and teaching theory", or GBLTT, a theoretical framework which measures learning outcomes based on gaming and learning procedures. GBLTT is focused on balancing information and gameplay as well as putting a focus on the ability of each learner to retain language competence and to put their subject to realistic situations